Determination of some Genetic indicators of Hybrids of sunflower Helianthus annuus L. - سليمان عروة; محمد نائل خطاب; نزار حربا (Latakia University Journal -Biological Sciences Series, 2023)
Five sunflower genotypes were planted (type 90 (A), model 19 (B), type 9 (C), type 54 (D), and baladi (E)), obtained from a previous (master) electoral program sourced from The General Authority for Agricultural Research in Damascus. In the field of a farmer in the al-Ghab area of ​​Hama governorate during the agricultural seasons 2020-2021-2022 according to a full reciprocal cross-hybridization program. The hybrid seeds obtained from the first season (20 hybrids) and the parents’ seeds were sown in a comparative experiment in the second season according to the RCBD randomized complete block design with three replications. The hybrid vigor was estimated compared to the parent average (HMP%) and the higher parent (HBp%) and the effect of reverse hybridization (RE%) for the characteristics of plant height (cm), stem diameter (cm), leaf area (m2), disk area (cm2), number of seeds per disc, and weight of 100 Seed (g), fertilization percentage (%), seed weight per plant (g), oil percentage (%), and oil quantity (g) at the level of one plant. This is to select the best hybrids in terms of high production and desirable traits, especially the percentage and quantity of oil, and to continue the superior ones to be introduced in the future in the breeding and improvement programs for this crop, as well as to determine the genetic origins that form with the mothers crosses that have the strength of the hybrid. The reverse hybrid (AXB) was distinguished in comparison with most of the studied hybrids with the highest significant values ​​as averages and the strength of the hybrid for the mean and the highest father and the reverse effect of the hybrid in several characteristics, the most important of which are: stem diameter (2.29 cm), and disk area (359 cm2) The number of seeds in the disc (1225 seeds), the weight of 100 seeds (6.12 g), the percentage of fertilization (84.6%), and the amount of oil (25.2 g per plant(. The reverse hybrid (CXD) also had the highest values ​​and high significance for the strength of the hybrid compared to the average of the two parents (HMP%) and the highest father (HBp%) and the effect of reverse hybridization (RE%) for the characteristics of seed weight per plant (135.67 - 130.99 - 24.38%, respectively) and the oil percentage ( 13.13 - 12.54 - 21.88%, respectively) and the amount of oil in plant seeds (175.71 - 174.93 - 57.14%). The results also showed that there is a function of cytoplasmic inheritance in the inheritance of the quantitative trait through the differences in the performance of both individual and reverse hybrids, which had an impact on the difference in the strength of the hybrid. We propose to grow the two hybrids (A X B) and (C X D) in the future with approved genotypes for the purpose of comparing them in other locations and seasons to ensure their stability and distinctiveness. We also suggest paying attention to cytoplasmic genetics and adopting the opposite effect when applying breeding programs.